2008
DOI: 10.1016/j.rgg.2008.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Permian magmatism and lithospheric deformation in the Altai caused by crustal and mantle thermal processes

Abstract: New structural and petrological data have been obtained for the zone of Siberia-Kazakhstan oblique collision for Permian time. In terms of classical tectonics, the area coincides with the Zaisan folded area produced by closure of the Char paleo-ocean in the Late Carboniferous. However, the extent, structure, and composition of magmatism at the Carboniferous-Permian (280±10 Ma) and Permian-Triassic (250±5 Ma) boundaries require an active control from Morgan-type lower mantle plumes (Tarim and Siberian plumes). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(58 citation statements)
references
References 11 publications
2
48
0
8
Order By: Relevance
“…Biotite from a tonalitic gneiss records an age of 270 ± 8 Ma. Other Ar-Ar age data from the Irtysh fault system (Vladimirov et al, 2008) are: 281 ± 2.4, 277 ± 7, 283 ± 7, 283 ± 1.6, 282 ± 1.5, 269 ± 2.3 and 264 ± 3 Ma. These age data record two events: a left-lateral ductile 285-270 Ma and a brittle-ductile 270-260 Ma (Briggs et al, 2007;Vladimirov et al, 2008).…”
Section: Chinese Altay Orogenmentioning
confidence: 99%
“…Biotite from a tonalitic gneiss records an age of 270 ± 8 Ma. Other Ar-Ar age data from the Irtysh fault system (Vladimirov et al, 2008) are: 281 ± 2.4, 277 ± 7, 283 ± 7, 283 ± 1.6, 282 ± 1.5, 269 ± 2.3 and 264 ± 3 Ma. These age data record two events: a left-lateral ductile 285-270 Ma and a brittle-ductile 270-260 Ma (Briggs et al, 2007;Vladimirov et al, 2008).…”
Section: Chinese Altay Orogenmentioning
confidence: 99%
“…Note that geographical North is at an angle relative to the figure's top. Intrusive complexes are indicated and colour-coded with respect to their inferred emplacement age (based on Vladimirov et al (2008), Wang et al (2009) andChen et al (2010)). Sample locations for this study are shown by yellow stars on the map.…”
Section: Figmentioning
confidence: 99%
“…Multi-mineral 40 Ar/ 39 Ar ages record two major stages of left-lateral deformation in the ISZ at $285-270 Ma and $270-260 Ma (Travin et al, 2001). It is thought that both the ISZ and CSZ accommodated more than 1000 km sinistral strike-slip displacement during this period of time (Melnikov et al, 1997;Burtman et al, 1998;Buslov et al, 2004;Vladimirov et al, 2008). The Rudny-Altai granitoids (NE of the ISZ) mainly have Devonian -Early Carboniferous crystallization ages (Fig.…”
Section: Introduction and Geological Settingmentioning
confidence: 98%
See 2 more Smart Citations